Thermal Characteristics of a Stratospheric Airship with Natural Convection and External Forced Convection - Tong Zhang; Shanshan Geng; Xin Mu; Jiamin Chen; Junyi Wang; Zan Wu (International Journal of Aerospace Engineering)
Though convective heat transfer is one of the main factors that dominate the thermal characteristics of stratospheric airships, there is no specific correlation equations for the calculation of convective heat transfer of airships. The equations based on flat plate and sphere models are all in use. To ameliorate the confusing situation of diverse convective heat transfer equations and to end the misuse of them in the thermal characteristic analysis of stratospheric airships, a multinode steady-state model for ellipsoid airships is built. The accuracy of the five widely accepted equations for natural convective heat transfer is compared and analysed on the proposed large-scale airship model by numerical simulation, so does that of the five equations for external forced convective heat transfer. The simulation method is verified by the available experimental data. Simulation results show that the difference of the five natural convection equations is negligible, while that of the five external forced convection equations must be considered in engineering. Forced convection equations with high precision and wide application should be further investigated.